2020
DOI: 10.1177/2042018820926000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin in obesity treatment in different populations: a meta-analysis

Abstract: Objective: Some studies have shown that metformin can reduce body weight. However, metformin has not been officially approved as a medicine for weight loss because its effect on different populations remains inconsistent. This meta-analysis aimed to summarize the weight loss effect of metformin quantitatively. Method: The randomized controlled and high-quality case-control trials of metformin monotherapy in obesity treatment were eligible. Baseline body mass index (BMI) was chosen as a self-control to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…Finally, the T2D therapeutic management is likely to play a major role in the metabolic profiles; in this study, data from KSA showed that treatment with metformin only was associated with the lowest BMI, as compared to the treatment when insulin or gliclazide was added ( P = 0.06); however, the small sample size was a limiting factor for drawing a reliable conclusion. Metformin has been shown and is used to induce weight loss [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the T2D therapeutic management is likely to play a major role in the metabolic profiles; in this study, data from KSA showed that treatment with metformin only was associated with the lowest BMI, as compared to the treatment when insulin or gliclazide was added ( P = 0.06); however, the small sample size was a limiting factor for drawing a reliable conclusion. Metformin has been shown and is used to induce weight loss [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…at both low (250 mg/kg) and high dose (500 mg/kg) was able to decrease the body weight to some extent. Metformin was used as a standard drug, which is well known to reduce body weights [ 35 ]. Interestingly, the ability of SC.Cr.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperglycemia-related inflammation and oxidative stress are closely associated with IR and all these abnormalities affect beta cell leading to its secretory dysfunction and increased apoptosis resulting in T2DM development and progression [ 41 , 105 , 106 ]. Moreover, studies show that metformin slightly reduces body mass and arterial blood pressure in overweight and obese people [ 107 , 108 , 109 ]. It may also improve lipid profile and balance between profibrinolytic and anti-thrombotic factors [ 5 , 110 ].…”
Section: Pleiotropic Effects Of Metforminmentioning
confidence: 99%